Indoor Residual Spraying (IRS) and Climate Variability on Malaria Burden in Vhembe district, Limpopo Province, South Africa from 2005 - 2015 - Bornman, Maria S. (Riana) (2026)
Dissertation (MSc (Public Health))--University of Pretoria, 2018.